(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2015)
The article is researched the traditional features of folk stories and legends about starvation of 1921-1922, 1932-1933, 1946-1947th. The author focuses on semantic and structural peculiarities of folklore genres that reflect people’s concept of tragic historical events of the twentieth century. Studies indicate active existence of these works within traditions and folklorization facts of unwritten history.